WESTERN HEROISM AS CULTURE IDEOLOGY IN THE AVANGERS - Feni Fasta; Christina Arsi; Lestari Lestari (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2015)
This paper is about the heroism of the probe in a pop culture product is The Avenger movie depicting the ideology of western culture. The use of theory in a study of communication in the process of production of meaning, through the film as a product of pop culture that will depict heroism as an ideology of Western culture. The method used in this paper is a critical discourse analysis of Teun A. VanDijk. It refers to the three levels of discourse structure, namely the macro-structure, super structure, and micro structure. The results shown in this paper is the analysis by describing the mask of the hero who displayed is actually just a cover for attracting all mankind to enter the world of